Program Pengembangan Kompetensi Entrepreneurship bagi Generasi Muda Putus Sekolah Menuju Kemandirian Finansial (Fokus Pada Anak Muda Putus Sekolah) - Syarifah Maihani; Yusrawati; Rossy Azhar; Zahraini; Emi Safrina; Fina Rizki (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2025)
The improvementt of entrepreneurship competency is an initiative to empower the young generation of school dropouts to achieve financial independence through entrepreneurship. This program is motivated by the high dropout rate in Indonesia due to family economic constraints. The main objective of this community service activity is to equip participants with practical entrepreneurial knowledge and skills, as well as develop an innovative entrepreneurial mindset. The method of implementing activities was in the form of intensive training, business mentoring, and the formation of weekly discussion groups. A total of 50 young school dropouts participated in this activity. The provided materials included the basics of entrepreneurship, financial management, digital marketing, and product development. This program provides access to initial capital through a partnership scheme with microfinance institutions. The results achieved were the formation of 10 small business groups, the birth of 15 young entrepreneurs who started businesses, and the creation of a support system network between participants. This program contributes to reducing unemployment among young school dropouts and improving the socio-economic status of participant families. Sustainability is carried out through a continuous mentoring system and periodic evaluation to ensure the development of participants' businesses.